2021
DOI: 10.30743/ll.v5i2.4445
|View full text |Cite
|
Sign up to set email alerts
|

Meaning-Making of Internet Memes to Create Humorous Sense: Functions as Speech Acts

Abstract: This research explored how the memes were created with multimodal elements that could make meaning to create a humorous sense and function as speech acts. With the complexity of meaning-making, nowadays, it had become a trend that people could communicate online through Memes. Semiotics provides how the combination of modes, media, and potential meanings, that were applied to make meaning in memes. At the same time, pragmatics proposes details on how memes can function as speech acts. This research adopted a q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In another case, speech function and speech act specify the communication's social purpose, and up to now, there had been a number of research into these contexts, such as Derakhshan & Arabmofrad (2018), Kauffeld & Goodwin (2022), Lee (2022), Oluoch (2020), Rakaj (2022), Santosa & Kurniadi (2021), Susilawati (2019), Uspayanti, (2020), Nita & Lestari (2021). It indicates that when people want to speak differently in different social situations, they are concerned with recognizing the social uses of language and how it is employed to communicate social meaning.…”
Section: Introductionmentioning
confidence: 99%
“…In another case, speech function and speech act specify the communication's social purpose, and up to now, there had been a number of research into these contexts, such as Derakhshan & Arabmofrad (2018), Kauffeld & Goodwin (2022), Lee (2022), Oluoch (2020), Rakaj (2022), Santosa & Kurniadi (2021), Susilawati (2019), Uspayanti, (2020), Nita & Lestari (2021). It indicates that when people want to speak differently in different social situations, they are concerned with recognizing the social uses of language and how it is employed to communicate social meaning.…”
Section: Introductionmentioning
confidence: 99%
“…By doing so, this study could fill the gap by analysing Malaysian memes from a multimodal discourse perspective, specifically on the latest issue on Siakap Langkawi in Malaysia since no study as explored this issue. Multimodality allows researchers to examine the way memes are created with multimodal texts as well as the way elements in the semiotic resources such as framing, salience, colour, and position create intended meaning in order to reach out to audiences (Nita et al, 2021). Therefore, it is only through an indepth multimodal analysis of the memes from a linguistic perspective that we are able to fully comprehend the way Malaysian social media users communicate their thoughts on the Siakap Langkawi issue.…”
Section: Figure 1 Meme Production Processmentioning
confidence: 99%
“…Motivated by their virality and ubiquity as the lingua franca of online communication and their unique aim that extends beyond inciting internet humor to become a form of "appropriation and resistance to dominant media messages", IMs became the subject of abundant research (Huntington 2013: 3;Nissenbaum and Shifman 2018). Different perspectives were adopted in researching this new genre such as the systemic perspective which investigates IMs as a system of signs representing a uniform movement in predetermined paths to cater for the netcitizens' expectations (Cannizzaro 2016 as cited in Zollinger 2021); the pragmatics perspective which concluded that the constative (for the expression of emotions) and the directive (for questioning issues) are the two main illocutionary acts by IMs (Nita, Setiawan and Lestari 2021); the multimodal pragmatics perspective which focuses on exploring the integration of semiotic resources for the interpretation and the construction of meaning (Mahfouz 2021); the generic perspective which foregrounds studying IMs' adherence to a template of specific generic rules (Dancygier and Vandelanotte 2017); finally, the cognitive perspective which studies the use of metaphors and metonymies in IMs (Younes and Altakhaineh 2022;Elyamany 2023). Nevertheless, there is a dearth of contrastive research across different languages on IMs as a genre marked by complex communication affordances in delivering meaning and creating humor.…”
Section: Introductionmentioning
confidence: 99%